2015
DOI: 10.1590/1414-431x20144191
|View full text |Cite
|
Sign up to set email alerts
|

Combined aliskiren and L-arginine treatment has antihypertensive effects and prevents vascular endothelial dysfunction in a model of renovascular hypertension

Abstract: Angiotensin II is a key player in the pathogenesis of renovascular hypertension, a condition associated with endothelial dysfunction. We investigated aliskiren (ALSK) and L-arginine treatment both alone and in combination on blood pressure (BP), and vascular reactivity in aortic rings. Hypertension was induced in 40 male Wistar rats by clipping the left renal artery. Animals were divided into Sham, 2-kidney, 1-clip (2K1C) hypertension, 2K1C+ALSK (ALSK), 2K1C+L-arginine (L-arg), and 2K1C+ALSK+L-arginine (ALSK+L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…In our study, we also observed that losartan inhibited Ang II-induced contractions. Santuzzi et al [27] observed that losartan reduced Phe-induced contractions, similar to the results of our study. Accorsi-Mendonça et al [28] observed that the ACE inhibitor trandolapril treatment decreased the Ang II-and Phe-induced but not KCl-induced contractions on isolated carotid arteries in rats.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we also observed that losartan inhibited Ang II-induced contractions. Santuzzi et al [27] observed that losartan reduced Phe-induced contractions, similar to the results of our study. Accorsi-Mendonça et al [28] observed that the ACE inhibitor trandolapril treatment decreased the Ang II-and Phe-induced but not KCl-induced contractions on isolated carotid arteries in rats.…”
Section: Discussionsupporting
confidence: 93%
“…In ischaemic muscles, aliskiren significantly increased vascular density, enhanced expression of eNOS and reduced oxidative stress levels, which is not dependant on blood pressure lowering effect . In Hypertensive rats induced by clipping the left renal artery, aliskiren was effective in preventing endothelial dysfunction and reduction endothelial oxidative stress . In hypertensive dTGR (double‐transgenic rat) harbouring human renin and angiotensinogen genes, aliskiren improved the remodelling of resistance arteries, which might be ascribed to the enhanced expression of eNOS and reduced oxidative stress by aliskiren .…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential mechanisms of aliskiren have not been well elucidated. Combination of aliskiren and l ‐arginine (a precursor of nitric oxide, NO) reduced contractile response to phenylephrine and improved acetylcholine relaxation in aortic rings 2‐kidney, 1‐clip (2K1C) hypertension . Associated with the fact that NO plays an important role in the pathogenesis of myocardial I/R injury, enhancing bioactivity of NO has emerged as an attractive target of novel drugs to attenuate I/R injury and improve endothelial dysfunction .…”
Section: Introductionmentioning
confidence: 97%
“…One recent addition to the family of RAAS blockers was Aliskiren, which is a DRI that is indicated for the treatment of hypertension. Several studies demonstrated that Aliskiren, as first orally active DRI, could be used as a monotherapy and in combination with other agents to lower blood pressure (24). Some studies estimated that once daily Aliskiren administration reduced hypertension compared with ACEI, ARB, and diuretics (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%